ASSESSING POLICY TRADEOFFS AND SILOS IN REGULATING PLATFORM POWER, PLATFORMIZATION, AND DATAFICATION - Popiel, Pawel (AoIR Selected Papers of Internet Research, 2023)
A key concern in international policy debates about articulating oversight of digital platform markets involves policy silos, arising from the scope of platformization and datafication, and the challenges in defining their policy boundaries and coordinating a comprehensive policy response. This paper examines how policymakers grapple with the problem by looking at a growing number of expert inquiries on digital platforms—a proxy for the international policy debate—that focus on policy problems ranging from market dominance to privacy risks to the spread of disinformation. Specifically, the paper develops a schema of related policy silos and tradeoffs that arise in these debates: 1) policy area silos, 2) market / sectoral silos, 3) temporal silos, and 4) normative tradeoffs. Then, it critically examines the implications of these silos and tradeoffs for policy interventions aimed at addressing concerns related to datafication and platformization, raising key questions about the scope of and assumptions underlying platform regulation internationally and noting the way they constrain policy design and thwart more holistic policy solutions.